Sobre José Luis Aguilar Guajardo, La ganadería en el Nuevo Santander, 1757-1795 (Ciudad de México: Colofón; Universidad Autónoma de Tamaulipas, 2020). - Gutiérrez Cañada, Diana Xóchitl (Septentrión, 2022)
Reseña